Photostory—A “Stepping Stone” Approach to Community Engagement in Early Child Development - Gaidhane, Abhay; Holding, Penny; Shah, Minal; Patil, Manoj; Telrandhe, Shital; Jadhav, Navnita; Kogade, Priti; Chaudhari, Sonali; Zahiruddin, Quazi Syed (Frontiers in Public Health, 2020)
Background: Capturing real-life practices through photographs provides an opportunity to create awareness and focus discussions on relevant issues in community. Photographs and narratives also engage decision makers, inspiring changes in policy and practice. Objective: Paper describes development and adaptation of an integrated photostory approach documenting actions and stimulating positive change in Early Child Development (ECD). Methodology: The Photostory method was built through a cyclical process to describe and explore early-childhood practices in central-India through photographs and stories. A systematic format to capture, archive and evaluate photographic material was developed. A standardized rating system was established to monitor levels of, and change in, community practices. We integrated Photostory process into routine visits undertaken during implementation of Stepping-Stones, an ECD intervention program. This paper utilized collected data to explore utility of rating framework to describe and measure behavior and to track change. We explored role of Photostory approach in engaging community in process of stimulating positive ECD experiences. Results: We developed a systematic framework to support data capture, analysis, and data utilization using multistep iterative mixed method process. A total of 161 Photostories were collected (72 at baseline and 89 at endpoint). Using a rating system which measured both the structure of the tasks, and the emotional engagement of the child and parent, many activities and practices observed were evaluated as providing at least an adequate learning space. In exploring change over the implementation process, at endpoint children were more likely to be observed as more engaged in their play activities (p < 0.05). Parental engagement levels remained stable, toward being less actively engaged. At endpoint we observed a trend toward activities being provided for children at a level of difficulty higher than child's level of developmental. The data provided the intervention team with local examples through which to engage parents in discussions on activities that stimulate effective child exploration and learning. We were also able to demonstrate the added value of photographs in stimulating detailed discussion amongst community members on early child development. Conclusion: Photostories can provide a systematic and rigorous methodology to stimulate engagement, monitor and measure change in community-based parenting interventions.